Legal Analysis of the Crime of Premeditated Murder and Theft (Decision Study Number 81/Pid.B/2023/Pn.Dps - I Putu Edi Rusmana; Bagus Gede Ari Rama (Institute Of computer Science (IOCS), 2024)
This article aims to analyze a criminal case, especially one that focuses on murder and robbery, as well as discussing the relevant law applied to the case. This research is normative legal research, which specifically includes examination and analysis of library materials, court decisions, or secondary data. The methods used include legal, factual, conceptual and interpretive approaches. This research focuses on the problems that occurred, first, how to prove the elements of the crime of murder and theft in case Number 81/Pid.B/2023/Pn.Dps? and the second problem is what are the legal implications applied to case Number 81/Pid.B/2023/Pn.Dps? After analysis, it has been proven legally and convincingly by the defendant that they committed murder as stated in Article 339 of the Criminal Code Jo. Article 55 section (1) which concerns criminal acts prior to murder. The legal consequence of this case is that defendant NSP was sentenced to 18 years in prison and R was sentenced to 20 years in prison. R received a longer prison sentence than NSP due to his previous criminal record of repeated theft